Perceived Discrimination sebagai Mediator Hubungan antara Akulturasi dan Kesejahteraan Psikologis pada Mahasiswa Etnis Tionghoa - Gosyen Lazero Annan; Marselius Sampe Tondok (Keluwih: Jurnal Sosial dan Humaniora, 2022)
Abstract—The purpose of this research wastoexamine the relationship between acculturation and the psychological well-being of ethnic Chinese students with perceived discrimination as a mediator. This study used quantitative methods, with a cross-sectional survey design. The respondents (N=97) were ethnicChinese students studying at public universities, selected using purposive sampling. The data was collected online using the Vancouver Index Acculturation (VIA), Brief Perceived Ethnic Discrimination Questionnaire-Community Version (Brief PEDQ-CV), and Psychological Well-Being Questionnaire (PWB-42). The results of the mediation test showed that perceived discrimination was a full mediator in the relationship between acculturation and the psychological well-being of ethnic Chinese students studying at public universities (z=-1.988; p <0.05).This finding revealed that as a minority, ethnic Chinese students accepted or adapted to the majority culture to reduce discrimination and this mechanism could improve their psychological well-being.The theoretical and practical implications of this research are discussed further. Keywords: acculturation, psychological well-being, perceived discrimination, chinese ethnicity Abstrak—Penelitian bertujuan menguji hubungan antara akulturasi dengan kesejahteraan psikologis mahasiswa etnis Tionghoa dengan perceived discrimination sebagai mediator. Penelitian ini menggunakan metode kuantitatif, dengan design cross sectional survei. Partisipan penelitian (N= 97) merupakan mahasiswa etnis Tionghoa yang berkuliah di perguruan tinggi negeri. Metode sampling yang digunakan yaitu purposive sampling. Pengumpulan data menggunakan tiga skala yaitu Vancouver Index Acculturation, Brief Perceived Ethnic Discrimination Questionnaire-Community Version (Brief PEDQ-CV), danPsychological Well-Being Questionnaire (PWB-42). Hasil uji hipotesis dengan uji mediasi menunjukkan bahwa perceived discrimination menjadi mediator full terhadap hubungan antara akulturasi dengan kesejahteraan psikologis mahasiswa etnis Tionghoa yang berkuliah di perguruan tinggi negeri(z=-1.988; p <0.05).Temuan ini menunjukkan bahwa sebagai minoritas, mahasiswa etnis Tionghoa melakukan penerimaan atau adaptasi terhadap budaya mayoritas untukmenurunkandiskriminasi yang dihadapinya dan mekanisme ini dapat meningkatkan kesejahteraan psikologisnya. Implikasi teoritis dan praktis penelitian ini, didiskusikan lebih lanjut. Kata kunci: akulturasi, kesejahteraan psikologis, diskriminasi yang dirasakan, etnis tionghoa